Increased dehydroepiandrosterone (DHEA) is associated with anxiety in adolescent girls - Mulligan, Elizabeth M. (Psychoneuroendocrinology, 2020)
The pubertal period is a time of rapid increase in the incidence of anxiety disorders, and thus, pubertal hormones may play a role in the precipitation of anxious psychopathology. DHEA, a steroid hormone that surges in adolescence, has been previously linked to anxiety, although the direction of this effect has been mixed. Using a cross-sectional design in a sample of 286 adolescent girls, the present study examined associations between salivary DHEA concentrations and self-report and interview-based measures of anxiety while controlling for pubertal status, menarche status, assessment time of day, and other hormones including testosterone, estradiol, and progesterone. Increased salivary DHEA concentrations were associated with more self-reported anxiety symptoms, increased anxiety symptom counts based on clinical interview, and increased probability of an anxiety disorder. Out of all anxiety symptom domains examined, generalized anxiety disorder symptoms were the best predictor of salivary DHEA concentrations after controlling for pubertal development. Collectively, our findings suggest relevance for DHEA in the development of anxiety in the pubertal period, as well as a robust relationship between DHEA and emerging symptoms of pathological worry during adolescence. The present study underscores the importance of examining associations between DHEA concentrations and anxiety in longitudinal designs.